Multiculturalidade no ensino de Ciências em uma escola do município de Vila Bela da Santíssima Trindade – MT - Moreira, Lineuza Leite (2019)
The present thesis analyzes the multiculturality within the school context in association with Science teaching. It aims to understand how Science teachers who work in the Elementary Education and the Regular and Integrated Secondary School of a Maroon school located in the municipality of Vila Bela da Santíssima Trindade - MT construct their knowledge and address the Sciences in a multicultural space. The relevance is inserted in a movement for a contextualized education which considers the importance of Science teaching of teachers who are sensitive to diversity. The research is based on authors who approach Science teaching, multiculturalism, teacher knowledge, identity, teacher training and learning. The methodological option adopted is based on the assumptions of the narrative inquiry; four teachers and the management team participated in the research. The information was obtained from a questionnaire, the researcher and participant‟s field notes, document analysis, photographic record, observations and conversations that were later transcribed. The results point to a heterogeneous teaching staff, of multiple identity. The complexity present in this school, the way that it is organized in relation to the Quilombola School Education, diversity and Science teaching are revealed as the personal, professional and collective stories are narrated. Within this construction of meanings, many challenges and dilemmas are also revealed in a tridimensional space. Science teachers, who are participants in the research, recognize the differences in the context of their work, they recognize the other and the need to overcome stereotypes. By adopting in their practices, pedagogical actions which value and/or contextualize questions the students bring from their daily life, they manifest the recognition of the students‟ identity plurality, diversify their strategies, involve the students, allow them to position themselves, act as promoters of learning. Science teaching conceived in a multicultural perspective demands the redefinition of knowledge, practices and the teaching by teachers.